2016
DOI: 10.1016/j.jcrs.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a multimedia-assisted informed consent procedure on the information gain, satisfaction, and anxiety of cataract surgery patients

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 12 publications
2
76
0
1
Order By: Relevance
“…In terms of desire for information, both the control and intervention groups reported a high score; this suggests that, despite counselling in clinic, patients still wanted to receive more information. This resonates with findings from previous research that suggests patients a) have low level of understanding recollection of information given in clinic 7,14 and b) want more information than they felt they received. 20 Furthermore, studies have shown that information provision is a substantial factor influencing overall patient satisfaction; with perceived lack of information correlating to poorer satisfaction outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of desire for information, both the control and intervention groups reported a high score; this suggests that, despite counselling in clinic, patients still wanted to receive more information. This resonates with findings from previous research that suggests patients a) have low level of understanding recollection of information given in clinic 7,14 and b) want more information than they felt they received. 20 Furthermore, studies have shown that information provision is a substantial factor influencing overall patient satisfaction; with perceived lack of information correlating to poorer satisfaction outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Patients who watched the "expectations" video were found to be more satisfied following the surgery than those in the "anatomy" group. 13 With cataract surgery being the most frequently performed ophthalmic operation 14 , the presence of such a simple intervention to potentially reduce anxiety levels for such a large number of patients represents an important opportunity for health care providers to improve the service they offer. Videos have the added advantage of being able to show patients information in a way that is not possible verbally.…”
mentioning
confidence: 99%
“…In addition to patient satisfaction, patients' attitudes toward using multimedia PtDA program to supplement the consent process survey was created based on the main benefits of using multimedia PtDAs identified in the literature [5,[9][10][13][14][15][16][17]. The survey consisted of 6 items of a 5-point Likert-type agreement scale where 5= strongly agree and 1= strongly disagree.…”
Section: Patients' Perceptions About the Current Processmentioning
confidence: 99%
“…These evidence-based tools help people make informed decisions congruent with their personal values and preferences about their treatment options. Extensive work has been undertaken to test the effectiveness of PtDAs [3][4][5][6][7][8][9][10]. In a 2017 Cochrane review of 105 studies with 31,043 participants, the use of PtDAs helped patients feel clear about their personal values and improved the rate of patient engagement in the decision-making by reducing the proportions of undecided patients and passive decision makers compared to usual care [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation